Islamic leadership principles in project management : assessment of its applicability and strategies for the Public Works Department of Malaysia - Muhamad Rosdi Senam (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Government construction projects that are implemented by the Public Works Department of Malaysia henceforth referred as Jabatan Kerja Raya Malaysia (JKR) have been continuously tarnished with underperformance and failures to meet clients' expectations as evidenced by high percentages of delayed projects, completion with extension of time, extra costs and unsatisfactory quality of works. Effective leadership by the project manager is fundamental and one of the crucial factors to achieve successful project delivery. Previous empirical studies have indicated the positive impacts of Islamic leadership on organisational performance and produced positive outcomes in various sectors such as business, banking, etc. However, studies on the construction-related and project management fields are found to be rare. This triggered the motion that imbuing Islamic leadership principles (ILP) is an alternative to improve project delivery and to improve the rate of project success in JKR. This research is specifically intended to obtain empirical support on the assessment of the applicability of Islamic leadership principles in project management thereby in enhancing project success. Primary data were collected in four (4) stages in a sequence consisting of two (2) rounds of Modified Delphi survey, followed by a validation interview and finally an acceptance survey. The findings indicate that ILP are applicable to JKR project management hence guaranteeing project success. High level of consensus was achieved in all the constructs attributing to the ILP and its strategies. This research is therefore contributing to the academic and industry sectors in the following ways. Firstly, it is the first research of its kind in terms of empirical research on Islamic leadership in project management. Secondly, it provides empirical data that ILP are applicable and has positive impacts on enhancing the chances of project success. Thirdly, as JKR is the lead technical agency for project implementation, this study provides the basis for other related agencies to embrace ILP as an alternative to better manage their projects. Finally, this research is a breakthrough that opens up the door for wider similar researches in the future.